Loss of Mitofusin 2 Promotes Endoplasmic Reticulum Stress - Ngoh, Gladys A. (American Society for Biochemistry and Molecular Biology, 2012)
The outer mitochondrial membrane GTPase mitofusin 2 (Mfn2) is known to regulate endoplasmic reticulum (ER) shape in addition to its mitochondrial fusion effects. However, its role in ER stress is unknown. We report here that induction of ER stress with either thapsigargin or tunicamycin in mouse embryonic fibroblasts leads to up-regulation of Mfn2 mRNA and protein levels with no change in the expression of the mitochondrial shaping factors Mfn1, Opa1, Drp1, and Fis1. Genetic deletion of Mfn2 but not Mfn1 in mouse embryonic fibroblasts or cardiac myocytes in mice led to an increase in the expression of the ER chaperone proteins. Genetic ablation of Mfn2 in mouse embryonic fibroblasts amplified ER stress and exacerbated ER stress-induced apoptosis. Deletion of Mfn2 delayed translational recovery through prolonged eIF2α phosphorylation associated with decreased GADD34 and p58(IPK) expression and elevated C/EBP homologous protein induction at late time points. These changes in the unfolded protein response were coupled to increased cell death reflected by augmented caspase 3/7 activity, lactate dehydrogenase release from cells, and an increase in propidium iodide-positive nuclei in response to thapsigargin or tunicamycin treatment. In contrast, genetic deletion of Mfn1 did not affect ER stress-mediated increase in ER chaperone synthesis or eIF2α phosphorylation. Additionally, ER stress-induced C/EBP homologous protein, GADD34, and p58(IPK) induction and cell death were not affected by loss of Mfn1. We conclude that Mfn2 but not Mfn1 is an ER stress-inducible protein that is required for the proper temporal sequence of the ER stress response.